(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2014)
سأحاول في هذا البحث الكشف عن التصور الرشدي للحركة في المستوى النفسي الذي يعد النفس بمثابة محرك داخلي للبدن وبالوقت نفسه هي مبدأ محرك لذاته . وكذلك يعتبر ابن رشد النفس بمثابة جوهر بسيط ومن أهم خصائصها " التحريك ، المعرفة ، الإدراك ، التخيل ، الشعور "، وهذه العمليات يطلق عليها أسم " الإدراك الروحاني "، وعليه فإن النفس إنما تستقبل صور المحسوسات من الخارج عن طريق الحواس الخمس وتقوم بتحويلها إلى معاني عقلية مجردة عن المادة " معقولات ". وعليه يعتقد ابن رشد أن حركة النفس إنما هي بمثابة حركة روحانية وليست حركة جسمانية في المكان، وبذلك فإن النفس إنما هي بمثابة المبدأ الأساس لكل العمليات الفيزيولوجية " السمع ، البصر ، التذوق ، الشم ، الحس العام "، وبنفس الوقت فهي المبدأ لكل العمليات النفسية الداخلية " الشعور ، الانفعال ، الخوف ، العاطفة "، وكذلك فإن النفس مصدر أساسي للعمليات العقلية " الإدراك ، الإحساس ، التخيل ، المعرفة ". لذلك فإن النفس في التصور الرشدي للحركة هي بمثابة السبب الصوري والغائي والمحرك للإنسان العاقل في كل أفعاله " الحسية ، النفسية ، والعقلية،المعرفية " . In this research I’m going to expose Averroes naturity conception in the psychic level whence the spirit is considered an interior motive for the body and at the same time it is a principle motive for itself . In the other hand , Averroes considers the spirit as a simple core . one of its most important . properties is mobilization , knowledge , conception , imagination and feeling . these processes are called . spiritual conception In other side the spirit receives the objects pictures from outside by means of the five senses and try to transform them into abstract reasonable meanings of the material . therefore, Averroes explains the psych movement is such spiritual movement and not physical in a place . consequently the spirit is considered the main principle for all physical operations ( acoustic , sight , longliness , smell , the general sense ) simul taneously it is the rule for all psychic interior operations ( feeling , excitement , fear , passion ) It is also a main source for intellectual operations ( conception , sensation , imaginations , knowledge ) as a result the spirit in the maturity imagination of motion is considered the normal and objective reason . the motive for the sane man is his sensation . psycology and intellectual actions .